Peer and Client Environments: Ways to Increase Organizational Support for Sexual Minority Adolescents - Christine Regan; Mickie Swisher; Rosemary Barnett; Jane Luzar; Jeanna Mastrodicasa (EDIS)
FCS2269, a 3-page fact sheet by Christine Regan, Mickie Swisher, Rosemary Barnett, Jane Luzar, and Jeanna Mastrodicasa, is aimed at the staffs of organizations that serve youth. It will help staff at these organizations understand, consider, and assess the need for environments and policies that support the needs of sexual minority youth. Published by the UF Department of Family, Youth and Community Sciences, February 2007.